Greetings from the of the Scientific Editor of the Magazine „Slauga. Mokslas ir praktika“ - dr. Viktorija Piščalkienė, The Scientific Editor of the Magazine „Slauga. Mokslas ir praktika“ (Slauga. Mokslas ir praktika, 2020)
Greeting from the of the Scientific Editor of the Magazine „Slauga. Mokslas ir praktika“